Pengaruh Motivator Insentif pada Kinerja Karyawan dengan Kepercayaan Diri sebagai Pemediasi (Universitas Negeri Semarang, 2015)
The purpose of this study is to determine the influence of job satisfaction, work environment, and Organizational Citizenship Behavior on employee performance directly and indirectly that is mediated by Organizational Citizenship Behavior. The population in this study were all employees of PT Indonesian Knitting Factory Semarang is 168 employees. Samples used is 117 employees. The method of data collection by quetionares. Data analysis using path analysis. The conclusion of this study are influence of job satisfaction and work environment on organizational citizenship behavior, the influence of organizational citizenship behavior on employee performance and organizational citizenship behavior mediate the relationship job satisfaction and work environment on employee performance.